The Influence of Quality of Work Life and Job Satisfaction on Turnover Intention: a Case Study of PT Alami Fintek Sharia - Ryan Triandy; Zulbainarni, Nimmi; Sukmawati, Anggraini (Business Review and Case Studies, 2024)
Background:One important aspect in the growth of financial technology companies is human resources, and one of the challenges is attracting the best talent to join and retaining existing talents.Purpose:This research aims to examine the influence of quality of work life and job satisfaction variables on turnover intention through a case study of PT Alami Fintek Sharia. Design/Methodology/approach:The research utilizes a quantitative approach, using the samples of all 106 employees of PT Alami Fintek Sharia as respondents. Research data were obtained through a questionnaire and analyzed using SEM analysis techniques with the help of a PLS-SEM program.Finding/Result:The results of this research underscore three aspects. First, quality of work life has a positive and significant effect on job satisfaction. The better the quality of work life, the higher the job satisfaction. Conversely, poor quality of work life reduces job satisfaction. Second, quality of work life has a negative and significant effect on turnover intention. The better the quality of work life, the lower the turnover intention, and conversely, poor quality of work life increases turnover intention. Third, job satisfaction has a negative and significant effect on turnover intention. The better the job satisfaction, the lower the turnover intention, and conversely, poor job satisfaction increases turnover intention.Conclusion:It is necessary to strengthen the organizational development unit in companies with the aim of improving quality work life and job satisfaction factors, especially factors related to adequacy of resources, compensation, and rewards, as well promotion opportunities.Originality/Value (state of the art): PT Alami Fintek Sharia is one of the leading p2p lending sharia in Indonesia one of the key successes is focus on managing people.Keywords: job satisfaction, quality of work life, turnover intention, SEM-PLS, P2P lending